(untitled) (Bangladesh Journal of Plant Taxonomy, 2016)
Five species of Trifolium L. (T. repens L., T. pretense L., T. hybridum L., T. campestre Schreb., and T. dubium Sibth.) were analyzed used to evaluate the genetic diversity and their phenetic relationships using inter-simple sequence repeats (ISSR) markers. Overall, T. pratense exhibited higher variation than other species. 114 amplicons were produced by ISSR markers, of which 77 (67.5%) bands were polymorphic. T. dubium showed the low genetic variation. Total genetic diversity values (HT) varied between 0.333 and 0.487, for an average over all polymorphic loci of 0.282. On a perlocus basis, the proportion of total genetic variation due to differences among species (GST) was 0.380. This indicated that about 38.0% of the total variation was among species. The estimate of gene flow, based on GST, was very low among species of genus Trifolium (Nm = 0.816). An assessment of the proportion of diversity present within species, HPOP/HSP, indicated that about 95.8% the total genetic diversity was within species. T. pratense and T. hybridum were grouped together and this clade was sister with T. repens. Two remainder species with yellow flowers were grouped together. Information on genetic diversity for Trifolium is valued for the management of germplasm and for evolving conservation strategies. Bangladesh J. Plant Taxon. 23(2): 167-173, 2016 (December)